The forms and contexts of polished tools. Analysis of polished stones from the robert junghanns collection of the institute of Puerto Rican culture - Bodin Cruz, Nichole L. (2021)
This research was motivated by the need to identify the great stylistic variability of polished stones within the Robert Junghanns Archaeological Collection of the Institute of Puerto Rican Culture. The manufacture of lithic polished materials have an economic significance that allows the underestimation of the homogeneity for the basic subsistence strategy of different groups in history, an important role in relation to various survival needs. This typological-functional analysis of the lithic instruments found in the Collection tries to present, classify and describe a series of lithic implements (from an unknown origin) and establishing 7 classes of different artifacts according to the type, raw material, manufacturing techniques used and the morphology they possess.